2022
DOI: 10.1186/s12916-022-02280-w
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of the Stopping Elderly Accidents, Deaths & Injuries (STEADI) program fall risk screening algorithms among community-dwelling Thai elderly

Abstract: Background Fall risk screening using multiple methods was strongly advised as the initial step for preventing fall. Currently, there is only one such tool which was proposed by the U.S. Centers for Disease Control and Prevention (CDC) for use in its Stopping Elderly Accidents, Death & Injuries (STEADI) program. Its predictive validity outside the US context, however, has never been investigated. The purpose of this study was to determine the predictive validity (area under the receiver oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
2
11
0
1
Order By: Relevance
“…Quantitative evidence supports the above inference. Consistent with two prior studies [13,14], goodnessof-t of the predictive models in our research did not reach the common criteria for predictive models [30]. The low goodness-of-t of predictive models may be due to several possible reasons.…”
Section: Interpretation Of Ndingssupporting
confidence: 79%
“…Quantitative evidence supports the above inference. Consistent with two prior studies [13,14], goodnessof-t of the predictive models in our research did not reach the common criteria for predictive models [30]. The low goodness-of-t of predictive models may be due to several possible reasons.…”
Section: Interpretation Of Ndingssupporting
confidence: 79%
“…The multiple electronic layers required to complete the study consent form, and to access, and complete the patient-reported measures may have been barriers in this study. As the STEADI Falls Risk Screening Tool has shown no difference in falls risk screening compared to asking patients falls history, multiple falls, and fear of falling (Helsel et al, 2021;Loonlawong et al, 2022;Nithman & Vincenzo, 2019), these results suggest that quick in-clinic screening tools may better meet the patients' needs in this population. However, future studies need to investigate other electronic methods to reach this population, including direct text messaging, in comparison to in-clinic only methods.…”
Section: Discussionmentioning
confidence: 87%
“…Although the MFS may be simpler to implement and more widely used in general settings, the STEADI program's ability to customize interventions based on individual risk factors enhances its clinical applicability. 16 The findings emphasize the importance of considering specific patient populations and their distinct fall risk factors when selecting appropriate fall prevention tools and interventions.…”
Section: Discussionmentioning
confidence: 97%
“…Patients who take 12 seconds or more to complete the TUG test are considered at risk of falling. 16 The 30-Second Chair Stand test evaluates lower extremity strength and endurance using a chair ST stopping E elderly A accidents D deaths I injuries with a straight back and a 17-in seat height. Patients, with their arms crossed over their chest, perform repeated cycles of standing up and sitting down within a 30-second timeframe.…”
Section: Methodsmentioning
confidence: 99%